The Relationship Between the Duration of Diabetes Mellitus and Foot Self-Care - Yunica, Aulia; Saherna, Jenny; Hadrianti, Dessy; Mulyani, Sri (Papua Medicine and Health Science, 2025)
Diabetes mellitus is a chronic metabolic disease that poses a high risk of foot complications; therefore, foot self-care is an essential component of disease management. The duration of diabetes mellitus is presumed to be associated with foot self-care behavior; however, empirical evidence remains inconsistent. This study aimed to analyze the relationship between the duration of diabetes mellitus and foot self-care among patients with diabetes mellitus. A correlational analytic study with a cross-sectional approach was conducted, involving 136 outpatient diabetes mellitus patients selected using an accidental sampling technique. The duration of diabetes mellitus was obtained from medical records and confirmed through self-reported data, then categorized into less than six months and more than six months, while foot self-care was measured using a questionnaire that had been tested for validity and reliability. Data were analyzed using univariate and bivariate analyses with the Chi-square test at a significance level of 0.05. The results showed that most respondents had been living with diabetes mellitus for more than six months and demonstrated good foot self-care behavior. A significant relationship was found between the duration of diabetes mellitus and foot self-care (p = 0.049). These findings indicate that disease duration is associated with foot self-care behavior; therefore, the duration of diabetes mellitus should be considered in planning foot care education for patients with diabetes mellitus.